2010
DOI: 10.1103/physrevb.82.104518
|View full text |Cite
|
Sign up to set email alerts
|

Self-doping effect and successive magnetic transitions in superconductingSr2VFeAsO3

Abstract: We have studied a quinary Fe-based superconductor Sr 2 VFeAsO 3 by the measurements of x-ray diffraction, x-ray absorption, Mössbauer spectrum, resistivity, magnetization, and specific heat. This apparently undoped oxyarsenide is shown to be self-doped via electron transfer from the V 3+ ions. We observed successive magnetic transitions within the VO 2 layers: an antiferromagnetic transition at 150 K followed by a weak ferromagnetic transition at 55 K. The spin orderings within the VO 2 planes are discussed ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
47
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 39 publications
11
47
2
Order By: Relevance
“…On the other hand, it is still unclear why superconductivity emerges in stoichiometric Sr 2 VO 3 FeAs, but not in Sr 2 ScO 3 FeAs. A self-doping effect through V 3þ /V 4þ mixed valence has been suggested from X-ray absorption spectroscopy [65]. Combined X-ray and neutron diffraction experiments verified the ideal stoichiometry, but showed also sensitivity to intrinsic V-doping of the iron site, which suppresses superconductivity in Sr 2 VO 3 [Fe 0.91(1) V 0.09 (1) ]As [66].…”
Section: Basic Crystal Structuresmentioning
confidence: 91%
“…On the other hand, it is still unclear why superconductivity emerges in stoichiometric Sr 2 VO 3 FeAs, but not in Sr 2 ScO 3 FeAs. A self-doping effect through V 3þ /V 4þ mixed valence has been suggested from X-ray absorption spectroscopy [65]. Combined X-ray and neutron diffraction experiments verified the ideal stoichiometry, but showed also sensitivity to intrinsic V-doping of the iron site, which suppresses superconductivity in Sr 2 VO 3 [Fe 0.91(1) V 0.09 (1) ]As [66].…”
Section: Basic Crystal Structuresmentioning
confidence: 91%
“…Recently, Cao et al suggested that the ordered moment is absent at the Fe site, and Tegel et al showed the possible incommensurate magnetic ordering of V moment with a propagation vector of q = (0, 0, 0.306). 31,32) Unfortunately, it is difficult to address the magnetic structure form the present NMR spectrum, because we cannot obtain the hyperfine coupling constants at present. However our experiments strongly suggest that the existence of the magnetic ordering and the change in the magnetic state at ∼ 70 K. Cao et al also observed two magnetic transitions at ∼ 150 K and ∼ 55 K.…”
Section: Methodsmentioning
confidence: 99%
“…22 Since the Fe Mössbauer spectra showed no additional broadening below T M , it was proposed that the anomaly originates from the V spin ordering. 22 However, the reported Fe Mössbauer spectra split into two peaks even above sealed in a silica tube with 0.2 bar of Ar gas and followed by a heat treatment at 1150…”
mentioning
confidence: 99%